Aplikasi Pupuk Urea, Pupuk Hayati Penambat Nitrogen Dan Amelioran Untuk Meningkatkan pH, C-Organik, Populasi Bakteri Penambat Nitrogen dan Hasil Jagung pada Inceptisols - Mieke Rochimi Setiawati; Yudith Silfani; Nadia Nuraniya Kamaluddin; Tualar Simarmata (Fakultas Pertanian Universitas Padjadjaran, 2020)
Inceptisols is known as one of the less-fertile dryland soil order that is widely used for corn cultivation. Proper type and dose of fertilizer can overcome the plant nutrition deficiency and increase corn yield in Inceptisols. This research aimed to examine whether the application of Urea with different doses, N-fixing biofertilizer and ameliorant can affect pH, Organic C, N-fixing bacteria population, and corn yield. The research was conducted at Balai Pengembangan Benih Hortikultura dan Aneka Tanaman Pasir Banteng, Jatinangor from January to June 2020. This research used Randomized Block Design with 16 treatments. The result showed that application of Urea with different doses, N-fixing biofertilizer and ameliorant significantly affected N-fixing bacteria population and corncob weight. 40% dose of Urea and 2 ton ha-1 ameliorant gave the best increase in corncob weight per plant of Bisi-2 by 345 g.